Cryptocurrency trading - technical analysis - Drobil, Jakub; Palovský, Radomír, 1959-; Fičura, Milan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2022)
The subject of the bachelor’s thesis "Cryptocurrency trading - technical analysis" is the analysis of the cryptocurrency space, how it is different to the traditional markets trading and exchange wise and what tools and indicators of technical analysis to use when trading it. The bachelor’s thesis focuses not only on all of that but also on creating trading strategies based on the tools of technical analysis, using manual and automatic backtesting. The aim of the work is to acquaint the reader with the basics of blockchain and how it is maintained, the cryptocurrency space and a few cryptocurrencies, the wide differences between cryptocurrency and traditional markets and technical analysis and its application to develop a suitable and ideally profitable trading strategy using various indicators. The data for the analysis is obtained from available internet sources that provide price development of cryptocurrencie together with technical indicators. The obtained values are processed in either the MS Excel program or TradingView strategy terminal, where the basic mathematical and logical functions are used. The data is then evaluated using the trading strategy and the optimal variant is found and back tested on new data to verify its profitability.
Vedoucí práce: Radomír Palovský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: informační média a služby [obor bakal. práce]; bakalářské práce; bachelor's theses